Various Techniques on Retrofitting for Earthquake Hazard Mitigation - Kok Wah, Choo; Zakaria, Rozana; Adnan, Azlan; Wai Yie, Leong (International Journal of Engineering and Technology, 2018)
Seismic tremors are a sudden vibration or trembling in the Earth that can be felt more than a few hundreds of kilometers. Quakes can twist the ground, making structures and non-structures crumple. Lives might be lost because of building deformation. Malaysia is a nation with low seismic movement. Be that as it may, Malaysia is surrounded by Philippines and Indonesia, which is two of the most seismically dynamic nations and certain level of surface waves, could be felt in our nation. Seismic tremor occasions have turned out to be more regular in this area. Seismic zone mapping for school located in Malaysia particularly in Johor Bahru can assist engineers to predict earthquake risk in building planning. Johor Bahru is situated in southern of peninsular Malaysia and is one of the urban areas with high population. School structures are considered as an essential structure since it contains a high numbers of pupils and teacher most of the time. The seismic zone mapping can recognize high possibly dangerous quake influenced area and essential risk mitigation method can be prepared. The seismic zone mapping not just ready to give designer to recognize region of higher earthquake risk but it can also be a good reference for future seismic safe building advancement.Â Â